CULTURAL SYMBOLS OF DONETSK REGION IN YEVHEN PETRYCHENKO’S CHORAL SYMPHONY-PERFORMANCE «ILLUMINATED BY THE BLACK SUN» - Yermolenko, Anastasiia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. One of the prominent figures among Donetsk artists is composer Yevhen Petrychenko, who frequently incorporates various cultural attributes of the region into his work. The use of symbolic elements in the choral symphony-performance «Illuminated by the Black Sun», which highlight the rich historical heritage of the region, challenges the stereotypical perception of Donetsk as merely an industrial area. The work has sparked significant response within the musical community, as evidenced by critical reviews of performances, numerous interviews with the composer and directors, and other discussions. However, analytical studies exploring the embodiment of the composition’s symbolic content are currently lacking. The main objective of the study is to explore the musical means of embodying the cultural symbolism of the Donetsk region in Yevhen Petrychenko’s choral symphony-performance «Illuminated by the Black Sun». The methodology is based on a culturological approach and includes historical-cultural and structural-analytical research methods. The main results and conclusions. The cultural symbols of the Donetsk region in Yevhen Petrychenko’s choral symphony-performance «Illuminated by the Black Sun» are more than artistic imagery; they embody the region’s rich cultural heritage and unique identity. This article provides a detailed analysis of all eight parts of the work, exploring how cultural symbols are expressed through musical language, structural elements, and performative techniques. Petrychenko harnesses musical expression to bring the work’s concept to life, integrating traditional and unconventional instruments, vocal exclamations, shouts, whispers, and theatrical choral staging. The piece stands as a significant contribution to contemporary Ukrainian culture, redefining Donbas as a vibrant cultural region and showcasing Petrychenko’s innovative approach to the grand choral cycle. Future research could pursue interdisciplinary approaches, blending musicology, theater studies, semiotics, and cultural analysis to further illuminate the role of cultural symbols in modern musical art